2015
DOI: 10.1007/s11262-015-1250-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of watermelon chlorotic stunt virus and tomato leaf curl Palampur virus mixed and pseudo-recombination infections

Abstract: Watermelon chlorotic stunt virus (WmCSV) and tomato leaf curl Palampur virus (ToLCPMV) are limiting factors for cucurbit production in south and southeastern Iran. ToLCPMV infects all cucurbit crops (except watermelons) whereas WmCSV is somewhat limited to watermelon, causing detrimental effects on fruit production. In a survey, we detected WmCSV in all watermelon growing farms in Fars province (southern Iran). Given that WmCSV and ToLCPMV are present in the same geographical location in Iran, we studied the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…During mixed infection, begomoviruses can also undergo pseudo-recombination (or reassortment), i.e., DNA-A and DNA-B components from two different viruses form a new association where the DNA-B is successfully replicated by the DNA-A encoded Rep protein. Both WCSV and SLCV have been, respectively, been found to pseudo-recombine (also referred to as reassortment) with the begomoviruses tomato leaf curl Palampur virus and cucurbit leaf curl virus [ 6 , 51 ]. However, to our knowledge pseudo-recombination between WCSV and SLCV have never been found in nature and have never been experimentally tested.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…During mixed infection, begomoviruses can also undergo pseudo-recombination (or reassortment), i.e., DNA-A and DNA-B components from two different viruses form a new association where the DNA-B is successfully replicated by the DNA-A encoded Rep protein. Both WCSV and SLCV have been, respectively, been found to pseudo-recombine (also referred to as reassortment) with the begomoviruses tomato leaf curl Palampur virus and cucurbit leaf curl virus [ 6 , 51 ]. However, to our knowledge pseudo-recombination between WCSV and SLCV have never been found in nature and have never been experimentally tested.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, viable pseudo-recombination has also been detected for the DNA-A and DNA-B of two tomato-infecting begomoviruses with different “iteron” sequences [ 54 ]. In previous reports of successful pseudo-recombination between WCSV and tomato leaf curl Palampur virus (ToLCPMV; [ 51 ]) and between SLCV and cucurbit leaf crumple virus (CuLCV; [ 6 ] the viruses shared similar iterons. It is possible that the iteron sequences are not the only factor contributing to the successful trans-replication of the WCSV DNA-B.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Central and southern Iran have subtropical climatic conditions, which is favorable for whitefly activities and therefore higher incidence of begomoviruses (Esmaeili et al 2015;Fazeli et al 2009;Kheyr-Pour et al 2000). Tomato and watermelon (main hosts of TYLCV and WmCSV, respectively) are extensively grown in Kerman, which is where we identified TYLCV and WmCSV in turnips.…”
mentioning
confidence: 80%
“…Following this we screened these samples for begomoviruses using the degenerate primer pair PCRv181 (Rojas et al 1993) and Bc (Deng et al 1994) and all were found to be PCR positive, yielding 550 bp amplicons. Furthermore, given that the begomovirus Watermelon chlorotic stunt virus (WmCSV) is also a major problem in Iran (Esmaeili et al 2015;Kheyr-Pour et al 2000), we tested these samples using the specific primer pair WmCSV-1440A-F (5′-ATC GAT TGT CCC AAC AAG GAC-3′) and WmCSV-2016A-R (5′-TTG CAA TCC GGG CCC ATC TTC-3′).…”
mentioning
confidence: 99%